Faktor Emotional Intelligence Dalam Keputusan Pembelian Produk (Studi Kasus Pada Mahasiswa Institut Alif Muhammad Imam Syafi’i) - Ziyadatus Shofiyah (At-Tasharruf "Jurnal Kajian Ekonomi dan Bisnis Syariah", 2025)
This study aims to explore the influence of Emotional Intelligence on product purchase decision making among students of Alif Muhammad imam Syafi'i Institute. The research method used is a qualitative approach with in-depth interviews and observations of students as research subjects. The results showed that students with high levels of emotional intelligence tend to be more selective, rational, and consider social aspects in making purchasing decisions. Self-awareness helps them in adjusting product choices to personal needs and values. Emotion management plays a role in preventing impulsive buying decisions due to emotional marketing strategies. Intrinsic motivation encourages students to choose products that can support their personal goals. Empathy makes them more likely to choose products from brands that have social responsibility, while social skills influence students' tendency to follow the recommendations of friends or influencers. The findings provide implications for marketers and manufacturers to design more effective marketing strategies by targeting the emotional and social aspects of college students. In addition, this study also underscores the importance of financial education for college students to increase their awareness in financial management and wiser consumption.